A Novel Intronic Pathogenic Variant in STAR With a Dominant Negative Mechanism Causes Attenuated Lipoid Congenital Adrenal Hyperplasia. (May 2021) - Finn, Erin; Kripps, Kimberly; Chambers, Christina; Rapp, Michele; Meeks, Naomi J. L.; Xu, Fang; Chen, Wuyan; Larson, Austin A.; Nokoff, Natalie J.
Lipoid congenital adrenal hyperplasia (LCAH) is typically inherited as an autosomal recessive condition. There are 3 reports of individuals with a dominantly acting heterozygous variant leading to a clinically significant phenotype. We report a 46, XY child with a novel heterozygous intronic variant in STAR resulting in LCAH with an attenuated genital phenotype. The patient presented with neonatal hypoglycemia and had descended testes with a fused scrotum and small phallus. Evaluation revealed primary adrenal insufficiency with deficiencies of cortisol, aldosterone, and androgens. He was found to have a de novo heterozygous novel variant in STAR : c.65-2A>C. We report a case of a novel variant and review of other dominant mutations at the same position in the literature. Clinicians should be aware of the possibility of attenuated genital phenotypes of LCAH and the contribution of de novo variants in STAR at c.65-2 to the pathogenesis of that phenotype.